Translation Strategies of Culture-Specific Terms in the Tourism Text â€œWisata Kuliner di Kota Batikâ€ - Zainal Arifin (Universitas Ahmad Dahlan, 2019)
The study aims to analyze and describe the translation strategies of culture-specific-words in the Indonesian tourism text Wisata Kuliner di Kota Batik into English Culinary Tour in the City of Batik. It used a descriptive-qualitative. The data were the specific-culture words, terms, or expressions in the text Wisata Kuliner di Kota Batik and its translation text Culinary Tour in the City of Batik. The data sources comprised the document and informants. The document was the tourism text of the GARUDA magazine, published by indomultimedia, Augustus 1st, 2010. The informants were the experts in translation linguistics. The data collection used a content analysis, in-depth interview, and questionnaires. The data validity employed a technique of data or source triangulation and peer debriefing. The data analysis applied an interactive model: data reduction, data display, and conclusion/verification. The results of the study showed that the translation strategies of the culture-specific words, terms, or expressions were as follows: 1) translation by cultural substitution, 2) translation by loanword with explanation, 3) translation by adoption with explanation, and 4) translation by loanword.Â